2021
DOI: 10.1002/cac2.12234
|View full text |Cite
|
Sign up to set email alerts
|

DNA crosslinking and recombination‐activating genes 1/2 (RAG1/2) are required for oncogenic splicing in acute lymphoblastic leukemia

Abstract: Background Abnormal alternative splicing is frequently associated with carcinogenesis. In B‐cell acute lymphoblastic leukemia (B‐ALL), double homeobox 4 fused with immunoglobulin heavy chain (DUX4/IGH) can lead to the aberrant production of E‐26 transformation‐specific family related gene abnormal transcript (ERGalt) and other splicing variants. However, the molecular mechanism underpinning this process remains elusive. Here, we aimed to know how DUX4/IGH triggers abnormal splicing in leukemia. Methods The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 74 publications
(165 reference statements)
1
27
0
Order By: Relevance
“…Second-generation sequencing technology has been rapidly developed in the field of precision medicine due to its advantages of high throughput, high sensitivity, ease of operation, and relative quantification [ 6 , 7 ]. Its development provides a large amount of data for medical research, which can be transformed into clinically relevant information to allow researchers to determine how genes affect phenotypes, following which genome editing technology can be used to directly manipulate almost any gene in various cell types and organisms to develop therapeutic strategies for diseases at the genetic level [ 8 , 9 ]. Mutations have been shown to play a vital role in various diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Second-generation sequencing technology has been rapidly developed in the field of precision medicine due to its advantages of high throughput, high sensitivity, ease of operation, and relative quantification [ 6 , 7 ]. Its development provides a large amount of data for medical research, which can be transformed into clinically relevant information to allow researchers to determine how genes affect phenotypes, following which genome editing technology can be used to directly manipulate almost any gene in various cell types and organisms to develop therapeutic strategies for diseases at the genetic level [ 8 , 9 ]. Mutations have been shown to play a vital role in various diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA-binding double homeobox 4 fused with immunoglobulin domain 1 and 2 (DUX4 1-150 -DNA ERG HD1-HD2) protein complexed with the expression recombinant gene (ERG ALT ) has its catalytic activity related to the interaction between Frontiers in Molecular Biosciences frontiersin.org the residues of the Linker A and Linker B of the DUX4 1-150 protein (Zhang et al, 2021). The mechanism of oncogenic biogenesis of ERG alt is activated when the atom OE2 of the residue Glu93 of Linker A establishes a strong hydrogen bond (around 2.20 Å) with the atom ND2 of the residue Asn41 of Linker B.…”
Section: Molecular Docking Of Dux4 1-150 -Dna Erg Hd1-hd2-697 Cellsmentioning
confidence: 99%
“…More importantly, the unexpected DUX4/IHG-mediated genomic instability is often associated with recombination-activating genes 1/2 (RAG1/2) recruitment onto the double tandem DRE-DRE sites, catalyzing V(D)J-like recombination and oncogenic splicings such as ERG alt , CLEC12A alt , and C6orf89 alt in leukemia. 4 Moreover, compared with the good prognosis for DUX4/ IGH, the recurrent MEF2D fusions are with a poor clinical outcome. The lack of effective therapy might be related to our poor understanding of the disease mechanism.…”
mentioning
confidence: 99%
“… 3 In addition, we also demonstrated that impaired DUX4-DRE interaction disrupted ERG alternative splicing (ERG alt ), also known as an important secondary hit in DUX4/IGH-type leukemia. In 2021, Zhang and co-workers 4 further showed that DUX4 homeobox domain HD1-HD2 might dimerize into a dumbbell-shaped trans configuration to crosslink two adjacent DRE sites. More importantly, the unexpected DUX4/IHG-mediated genomic instability is often associated with recombination-activating genes 1/2 (RAG1/2) recruitment onto the double tandem DRE-DRE sites, catalyzing V(D)J-like recombination and oncogenic splicings such as ERG alt , CLEC12A alt , and C6orf89 alt in leukemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation